L54 comparative study of the absorption and distribution of tocotrienols to tocopherols - Abd. Mutalib, Mohd Sokhini; Khaza'ai, Huzwah (2009)
Vitamin E is a potent fat soluble antioxidant that inhibits lipid peroxidation in biological membranes. In nature compounds with vitamin E activity are α, β, γ and δ- tocopherols and α, β, γ and δ- tocotrienols. Tocotrienols have been suggested to exert a hypocholesterolemic, antiatherosclerotic effect, anti-proliferative and suppressive effect on human breast cancer cells. Besides all the positive effects shown by tocotrienols, these compounds are known to have extremely low bioavailability and low bioaccumulation. A comprehensive knowledge of absorption, distribution, metobolism and elimination of this compund is important for the interpretation of pharmacological and toxicological effects it exerts. Therefore, this study was designed to trace the fate of both α- tocopherol and tocotrienols after 30 days' oral ingestion by Sprague Dawley rats. In this study the pharmacokinetic of tocotrienols found to be entirely different compared to tocopherols. Tocotrienols showed an adaption period, which was improved by the end of 30 days' supplementation in order to attain the selectivity of tocotrienols as a source of vitamin E for the body. Tocotrienols, however have a low accumulation pattern compared to tocopherols in various organs studied, except for skin and adipose tissue, suggesting a different mechanism of uptake between α- tocopherol and the tocotrienols involved. An in vitro study study confirmed the finding that a-TTP (α- tocopherol transfer protein) is highly expressed in hepatic cells, which evidently discriminate against bioavailability of tocotrienols in plasma. In an effort to elucidate the mechanism involved in uptake of tocotrienols by the cell, the expression of α-TPP in other cells (HepG2) was investigated. Expression of α-TPP in other cells related to where it is accumulated will be resumed as a continuation of the current work.